Budowa geologiczna i warunki hydrogeologiczne zbiornika antropogenicznego w okolicach Łęknicy (Łuk Mużakowa) = Geological structure and hydrogeological conditions of anthropogenic reservoir in the environs of Łęknica (Muskau Arc) - Gontaszewska-Piekarz, Agnieszka; Kraiński, Andrzej; Jachimko, Barbara; Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paper presents an outline of geological structure of Muskau Arc and detai led description of its part. Investigation covered area of former brown coak mine, now anthropogenic lakeland. Paper contains geological sections based on 25 m deep bore-holes. Also hydrogeological conditions and chemical properties of ground- and surface water were discussed.
Keywords: pojezierze antropogeniczne; Łęknica; węgiel brunatny; brown coal; anthropogenic lakeland